The Use of Immersive Virtual Reality for Vocabulary Acquisition: a Systematic Literature Review - Palmeira, Eduardo Gabriel Queiroz; Martin, Victor Biagiotti Saint; Gonçalves, Victor Barbosa; Moraes, Ígor Andrade; Lamounier Júnior, Edgard Afonso; Cardoso, Alexandre (Anais do Simpósio Brasileiro de Informática na Educação (SBIE), 2020)
Many teachers consider vocabulary acquisition a low intellectual activity. However, substantial time is needed for teachers and learners, in this subject, since there are vast numbers of words to be learned. In this context, it is expected that vocabulary acquisition assisted by Immersive Virtual Reality (IVR) can be a powerful learning method. Therefore, this paper aims to summarize the state-of-the-art concerning the use of IVR in vocabulary acquisition through a systematic literature review. Results pointed out that IVR enables autonomous learning with an increase in the speed of the educational process, and its use has shown higher effectiveness, positive attitudes, engagement, and motivation on the part of students.